VULNERABILITY ASSESSMENT TO CLIMATE CHANGE IN KRISHNA RIVER BASIN DISTRICTS OF ANDHRA PRADESH AND TELANGANA STATES - K. KRISHNA REDDY, K. GURAVA REDDY, M. CHANDRASEKHAR REDDY; K. PALANISAMI (The Journal of Research ANGRAU, 2015)
In the present paper vulnerability index was constructed by considering exposure, sensitivity and adaptive capacity. Principal component analysis was used in assessing the vulnerability index for the districts of Krishna river basin in Andhra Pradesh and Telangana. More than 60 percent of the area is vulnerable in the districts and Ananthapur district is highly vulnerable with an overall index of 5.15. Krishna district is less vulnerable in the basin with an index -3.61.The adaptation strategies from the highly vulnerable areas can be studied and implemented in the less vulnerable areas to minimize the impacts of climate change over the coming years. It is also important that climate awareness and capacity building of stakeholders become an integral part of the development programs at all levels.